Rhetorical mechanisms in the Holy Qur’an: “Surah Ad-Dukhān as a corpus” - arioua, arioua (El Omda in Linguistics and Discourse Analysis, 2025)
Rhetorical sciences have an effect in strengthening the pilgrims and the effects these sciences have on the recipient while they lead to an effects in submission and Submission, which is the result of persuasion, the more Content these Sciences Carry. likewise, if one wants to monitor the pilgrims from the rhetorical Point of view, he must its position within the science of rhetoric is monitored, and accordingly. What new Rhetoric Sees is that these sciences are linked to an issue that the Sender is trying to influence the recipient, the Purpose of these Sciences is a means, a goal, and the reasons for choosing the subject The importance of the subject of the pilgrims from a rhetorical standpoint. and the attempt to define modern critical theories and the extent of their application to the Holy Qur'an.